Alcohol and violence in nightlife and party settings: A qualitative study. (7th April 2016) - Pedersen, Willy; Copes, Heith; Sandberg, Sveinung
Abstract: Introduction and Aims: In 'binge drinking' cultures, there is a strong association between alcohol consumption and violence. At the same time, several studies suggest that this link is cultural and contextual. We explore the role of alcohol in incidents of violence in nightlife settings. Design and Methods: We used qualitative interviews with 104 Norwegians (52 men and 52 women, mean age 25 years) who binge drink and party in nightlife settings. Results: Alcohol both sparks and constrains violence in these contexts. When participants use alcohol, they expect conflicts to occur and blame alcohol intoxication for such behaviour. The packed settings of nightlife and parties combined with the effects of alcohol can induce violence through personal affronts, heightened emotions and jealousy. At the same time, nightlife settings constrain violence. That is, binge drinkers excuse misbehaviour when it is attributed to alcohol. In addition, audiences in these setting often go to great lengths to stop fights. Combined, these factors help explain why violence occurs and why it usually does not escalate. Discussion and Conclusions: The association between alcohol and violence can be understood by more closely examining the cultural and situational context where the events occur. This link is not primarily related to the psychopharmacological properties of alcohol, but rather it is associated with situational factors and cultural norms regarding how to behave while intoxicated. Strategies aiming at reducing violence in nightlife should take such factors into consideration. [Pedersen W, Copes H, Sandberg S. Alcohol and violence in nightlife and party settings: A qualitative study. Drug Alcohol Rev 2016;35:557–563]